Strafrechtliche Verantwortung im internationalen Kartellrecht Eine Untersuchung zu zwischenstaatlichen Verwerfungen infolge der Kriminalisierungsbewegung - Hildebrandt, Patrick (Münchener Schriften zum Europäischen und Internationalen Kartellrecht, 2016)
The book examines the conflict situations at international level arising from the spread of criminal sanctions in national competition law and thereby in particular deals with the risks linked to criminal law provisions of several countries being applicable to one and the same international cartel. Before analyzing these conflicts, the author examines to what extent treaties and instruments of international cooperation and coordination, both from the sphere of criminal law and the sphere of competition law, apply to the enforcement of national criminal competition law provisions.